Pengaruh Umur Perusahaan, Reputasi Underwriter, Reputasi Auditor, dan Financial Information terhadap Underpricing Perusahaan yang Melakukan Initial Public Offering (IPO) di BEI - Elparez, Reyhan; Mulyani, Erly (Universitas Negeri Padang, 2025)
The purpose of this study is to examine the influence of company age, underwriter reputation, auditor reputation, and financial information. The population is an IPO company listed on the Indonesia Stock Exchange for the period 2019 to 2022. Using the purposive sampling method, there were 78 companies as research samples. The type of data used is secondary data obtained from the official website of the Indonesia Stock Exchange and the official website of the Company. The hypothesis is a test using multiple linear regression analysis. The results showed that the age of the company, the reputation of the underwriter, the reputation of the auditor, and ROE had no effect on underpricing. and DER has an influence on underpricing.